Electric power system performance and its improvement : the case of Laos - Khene Thepvongsa; Malik, A. S.; Surapong Chiraratananon; Yu, Cun Yi; Sida (Bangkok : Asian Institute of Technology, 1996)
This study is to evaluate the past trend of technological and economic performance in the electric power system of Lao PDR. The technical indicators such as Laod factor, Plant capacity factor, system losses and system reliability are assessed to find the performance of existing EDL power system through an engineering approach. The economic performance only tariff structure, billing system and domestic load forecasting are discussed. This study has carried out the cost-benefit of a sample study for technical and economic improvement of NamNgum power plant and has calculated losses and cost-benefit of loss reduction in a sample distribution feeder. Finally, the general recommendations in the areas of power generation, transmission and distribution system, billing system and electricity tariffs are addressed to improve the efficiency of performance in the whole EDL system and specific cases.
Thesis (M.Eng.) - Asian Institute of Technology, 1996
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering.
Keywords: Electric power systems -- Laos -- Management